Temporal decorrelation by SK channels enables efficient neural coding and perception of natural stimuli - Chengjie G. Huang (Nature Portfolio, 2016)
The neural mechanisms underlying efficient coding of natural sensory stimuli have yet to be fully determined. Here, monitoring sensory pyramidal cells in weakly electric fish, the authors find SK channels are necessary for matching the responsiveness of neurons to natural stimuli and subsequent behavioural responses.